DHEA and sport - Corrigan, B. (Clinical Journal of Sport Medicine, 2002)
Dehydroepiandrosteron (DHEA), ein 19-Kohlenstoff-Steroid, wird zuerst vorwiegend von Bodybuildern begeistert angewandt, da es in der Lage ist, sich in Testosteron zu verwandeln. Die Begeisterung für seinen ergogenen Effekt nahm jedoch bald ab und somit auch sein Gebrauch unter den Sportlern. Hauptproblem ist, dass die Langzeitwirkungen unbekannt sind und viele hormonelle und endokrine Systeme beeinträchtigt werden können. Dehydroepiandrosterone (DHEA), a 19-carbon steroid, is situated along the steroid metabolic pathway. It is the most abundant circulating hormone in the body and can be converted to either androgens or estrogens. It is readily conjugated to its sulphate ester DHEAS, and they are designated as DHEA(S) here when used together. Its secretion reaches a peak in early adulthood and thereafter decreases, until approximately age 70 years when it reaches a concentration of approximately 20%. Many hormonal changes may take place with aging but none is as marked as this. This "relative DHEA deficiency" resulted in DHEA being enthusiastically labelled by some as a fountain of youth or an antidote to aging that would prove to be the panacea they are seeking. Its use was also taken up enthusiastically by the athletic community and used as a prohormone in the belief or hope that it would be converted mainly to testosterone in the body.